Should the Country Abolish Freedom of Religion to Counter Terrorism? Haruskah Negara Menghapus kebebasan Beragama Demi Melawan Teroris? - Susanto, Fransiska Ayulistya; Hidayat, M. Choirul (Universitas Muhammadiyah Sidoarjo, 2020)
This paper is offer an assessment of the situation regarding freedom of religion in Xinjiang China. It argues that the Xinjiang authorities and the China government responsible for freedom of religion violation under their counter terrorism action. Even though, the freedom of religion is derogable right however the reason shall be under the national security and public order situation but, what the government do is too far and could lead Uighur religion eradication. To investigate the Xinjiang authorities and China government action, the paper collects the data from many Non-governmental organization and United Nation Report and analysis the fact with the international regulation and national regulation that China follow or have.